Listening, Grammar and Reading Comprehension Skills of the Test of English as a Foreign Language: A Correlational Study - Sapoetra, Jimmy (Humaniora, 2017)
The article aimed to investigate whether there was a correlation among the language skills and components. The researcher took two language skills and one language component to be part of the research: listening, reading comprehension skills, and grammar mastery. In the research, there were several questions regarding the three variables of listening, reading, and grammar which were focusing on the correlation among the variables. The independent variable was grammar mastery (X) while the independent variables were listening comprehension (Y1) and reading comprehension (Y2). The data collection was taken from the population of Grade X Budi Luhur Senior High School students, Tangerang, with 40 students served as a sample. The research was conducted using the quantitative method with the help of statistical calculation of Pearson Product Moment Correlation to prove whether there was a significant correlation among the three variables. As a result, it is proven that there is no significant correlation between grammar mastery and both listening and reading skills while there is a quite strong correlation between listening and reading skills of the students.